Nkx2.2 and Arx genetically interact to regulate pancreatic endocrine cell development and endocrine hormone expression - Mastracci, Teresa L. (2011)
Nkx2.2 and Arx are essential pancreatic transcription factors. Nkx2.2 is necessary for the appropriate specification of the islet alpha, beta, PP and epsilon cell lineages, whereas Arx is required to form the correct ratio of alpha, beta, delta and PP cells. To begin to understand the cooperative functions of Nkx2.2 and Arx in the development of endocrine cell lineages, we generated progenitor cell-specific deletions of Arx on the Nkx2.2 null background. The analysis of these mutants demonstrates that expansion of the ghrelin cell population in the Nkx2.2 null pancreas is not dependent on Arx; however, Arx is necessary for the upregulation of ghrelin mRNA levels in Nkx2.2 mutant epsilon cells. Alternatively, in the absence of Arx, delta cell numbers are increased and Nkx2.2 becomes essential for the repression of somatostatin gene expression. Interestingly, the dysregulation of ghrelin and somatostatin expression in the Nkx2.2/Arx compound mutant (Nkx2.2(null);Arx(Δpanc)) results in the appearance of ghrelin+/somatostatin+ co-expressing cells. These compound mutants also revealed a genetic interaction between Nkx2.2 and Arx in the regulation of the PP cell lineage; the PP cell population is reduced when Nkx2.2 is deleted but is restored back to wildtype numbers in the Nkx2.2(null);Arx(Δpanc) mutant. Moreover, conditional deletion of Arx in specific pancreatic cell populations established that the functions of Arx are necessary in the Neurog3+ endocrine progenitors. Together, these experiments identify novel genetic interactions between Nkx2.2 and Arx within the endocrine progenitor cells that ensure the correct specification and regulation of endocrine hormone-producing cells.